Medicine effectiveness comparisons of different physicotherapeutics for stroke patients with dysphagia: A protocol for systematic review and network meta-analysis. Issue 38 (18th September 2020) - Li, Ying; Li, Runmin; Xiao, Jia; Hu, Yan; Xie, Rongrong; Yuan, Yanyan; Li, Dongying
Abstract: Background: Oropharyngeal dysphagia is a common disorder after stroke. Physical therapy has been widely used in the rehabilitation of patients with dysphagia after stroke. Due to the lack of randomized trials directly comparing the efficacy of various physical therapies directly, the relative efficacy of these methods is difficult to determined. Therefore, we intend to conduct a network meta-analysis to evaluate the benefits of these physical therapies. Methods: According to the retrieval strategies, randomized controlled trials (RCTs) on physical therapies for stroke patients with dysphagia will be obtained from CNKI, Wan Fang Data, PubMed, Web of science, Embase databases and Cochrane Library, regardless of publication date or language. Studies were screened based on inclusion and exclusion criteria, and the Cochrane risk bias assessment tool will be used to evaluate the quality of the literature. The network meta-analysis will be performed in Markov Chain Monte Carlo (MCMC) method and carried out with Stata14 and OpenBUGS14 software. Ultimately, the evidentiary grade for the results will be evaluated. Results: This study will compare the efficacy of physical therapies in the treatment of stroke patients with dysphagia and suggests a reasonable clinical choice. Conclusion: Our findings will provide references for future guidance developing and clinical decision.